2023
DOI: 10.3390/cells12020294
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and OLT1177 Cooperate in the Reduction of Melanoma Growth by Inhibiting STAT3 Functions

Abstract: The NLRP3 inflammasome is a multimolecular complex that processes inactive IL-1β and IL-18 into proinflammatory cytokines. OLT1177 is an orally active small compound that specifically inhibits NLRP3. Here, B16F10 melanoma were implanted in mice and treated with OLT1177 as well as combined with the glucocorticoid dexamethasone. At sacrifice, OLT1177 treated mice had significantly smaller tumors compared to tumor-bearing mice treated with vehicle. However, the combined treatment of OLT1177 plus dexamethasone rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Currently, OLT1177 and Tranilast inhibitors represent two promising pharmacological candidates in this setting. The combination of OLT1177 and dexamethasone affects the nuclear and mitochondrial isoforms of the signal transducer and activator of transcription 3 (STAT3), capable to shrink tumor growth [ 180 ]; alternatively, Tranilast, although though indirect links with NLRP3 inflammasome, has been proposed to inhibit melanoma cell proliferation by activating CD8 + T cells [ 181 ]. Ovarian cancer (OC) is the seventh most commonly diagnosed cancer among women [ 182 ].…”
Section: Involvement Of the Nlrp3 Inflammasome In Other Type Of Cance...mentioning
confidence: 99%
“…Currently, OLT1177 and Tranilast inhibitors represent two promising pharmacological candidates in this setting. The combination of OLT1177 and dexamethasone affects the nuclear and mitochondrial isoforms of the signal transducer and activator of transcription 3 (STAT3), capable to shrink tumor growth [ 180 ]; alternatively, Tranilast, although though indirect links with NLRP3 inflammasome, has been proposed to inhibit melanoma cell proliferation by activating CD8 + T cells [ 181 ]. Ovarian cancer (OC) is the seventh most commonly diagnosed cancer among women [ 182 ].…”
Section: Involvement Of the Nlrp3 Inflammasome In Other Type Of Cance...mentioning
confidence: 99%
“…11 OLT1177 is an orally available drug, currently in Phase 2 trials for gout, 12 with demonstrated Phase 1 safety in patients with cardiovascular disease. 13 Preclinical data also shows efficacy in treating multiple sclerosis, 14 Alzheimer's disease, 15 melanoma, 16 reperfusion injury, 17 intracerebral hemorrhage 18 and osteoarthritis. 19 As the evidence of its safety continues to grow, OLT1177 is emerging as an exciting new candidate.…”
Section: Introductionmentioning
confidence: 99%